Lecturers’ Perceptions on The Use of Sharia Credit Card - Nadhri Filka; Tuti Anggraini (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
The phenomenon of using credit cards for some people is considered a symbol of status and lifestyle. This has an impact on conventional and Islamic financial institutions to compete to create banking card products that function to attract the attention of potential customers. Therefore, this study aims to analyze the perception of lecturers in the use of Islamic credit cards. The sample of this research is people who have a teaching profession at an Islamic University. The research method is qualitative, then the data collection in this study is the distribution of online questionnaires and literature studies. Then the data is analyzed by interactive model. The results show that what makes lecturers less interested is that they think conventional and sharia credit cards are the same. Furthermore, the lack of socialization of Islamic banks in promoting and explaining in detail about Islamic credit cards. Then, someone who has a teaching profession has the perception that using a sharia credit card will give them financial risk if one day they fail to pay their bills. The services and facilities provided by Islamic banks are not maximized when compared to conventional ones.